Effect Of Soil Streptomyces On Seed Germination - P. VENKATACHALAM; J. RONALD; K. SAMBATH (International Journal of Pharma and Bio Sciences, 2010)
Microorganisms are abundant in soil possessing ability to produce economically valuable substances like enzymes, antibiotics, hormones, etc. Actinomycetes especially Streptomyces predominate organic soil. In the present study Streptomyces gibosonni, Streptomyces caerulius, Streptomyces viridochromogenes, Streptomyces gresioluteus and Streptomyces clavifer were isolated from different soil samples. Their effect on growth of crop plants and herbs was analysed. S.viridochromogenes and S.clavifer found to be inhibiting seed germination of crop plants while S.gibosonni and S.grieseoleutus induced seed germination.